Integrated Management of Wetlands: a Case Study on Asan Conservation Reserve, Uttarakhand, India - Hussain, Syed Ainul (Indian Forester, 2007)
Integrated wetland management is a process through which managers can develop a vision, agree on shared values and make informed decisions and act together to manage the natural resources of a river basin. The primary condition for achieving integrated wetland management is the willingness of sectoral stakeholders to work together. All stakeholders need to understand the endowment and value of water resources and learn on how to manage human needs without jeopardizing wetland functions. The present case study aims to highlight the interests and positions of the various stakeholders on the water management in the Asan Barrage and the initiatives taken by the Uttarakhand Forest Department in developing a water storage reservoir the Asan Barrage in to a 'Conservation Reserve' through consultative process and effective participation of stakeholders.